The Integration of Fuzzy Logic System for Obstacle Avoidance Behavior of Mobile Robot - Nur Ilyana Anwar Apandi (International Journal of Electrical Engineering and Applied Sciences, 2019)
A mobile robot has a capability of sensing its location under uncertain environment,planning a real-time path as well as controlling its steering angle and speed to reach the target location. A robust controller is embedded in mobile robot whilst analyzing the input and output that help it to navigate without colliding with any obstacles. Meanwhile, Fuzzy Logic Controllers (FLC) is an intelligent technique that proves to be the one of the most reliable controllers that suits well for nonlinear system like robot due to the simple control based on user input without any prior knowledge to the mathematical model. In this paper, the Mamdani and Sugeno FLC are developed for a mobile robot. The smoothness and efficiency that generated from these FLC is analyzed based on simulation of Pioneer P3-DX robot in virtual robotic software for single and multirobot environments under static obstacles environment. Simulation results for the Pioneer P3-DX robot shows the Sugeno FLC able to produce smoother path and reach the goal faster than Mamdani FLC.